COSMETIC MICROBIOLOGY: CURRENT STATE, CHALLENGES AND PROSPECTS - Петросова, Валентина (SWorldJournal, 2025)
The aim of this review was to summarize current concepts regarding microbiological aspects of the development, manufacturing and quality control of cosmetic products, as well as the role of the skin microbiome in the safety and efficacy of cosmetics. An